2022
DOI: 10.1029/2022gl101189
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Seasonal Shear Wave Velocity Changes in the Top 6 m at Garner Valley in Southern California With Borehole Data

Abstract: The properties and dynamics of shallow materials are of great importance for a wide range of topics including environmental seismology, seismic ground motion prediction and performance of infrastructure above and below the surface. Near-surface materials have extremely low shear wave velocities (V S ) of 100-400 m/s (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The main reason for the different resolved amplitudes is the smaller timestep used in the analysis done in the present study. Additional recent studies based on autocorrelations and small timesteps found significant daily and seasonal velocity variations of shallow materials in southern California and on Mars (Qin et al., 2022, 2023), with amplitudes similar to those resolved here. We speculate that significant daily and seasonal velocity variations of shallow materials are common at many other sites on Earth with sedimentary surface layers, and can be resolved with a high resolution analysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The main reason for the different resolved amplitudes is the smaller timestep used in the analysis done in the present study. Additional recent studies based on autocorrelations and small timesteps found significant daily and seasonal velocity variations of shallow materials in southern California and on Mars (Qin et al., 2022, 2023), with amplitudes similar to those resolved here. We speculate that significant daily and seasonal velocity variations of shallow materials are common at many other sites on Earth with sedimentary surface layers, and can be resolved with a high resolution analysis.…”
Section: Discussionsupporting
confidence: 86%
“…(c) Comparison between velocity changes estimated by Qin et al. (2022) (black line) and this study (red line). The two curves are obtained by smoothing raw data points within 1 week.…”
Section: Application To Observed Seismic Datamentioning
confidence: 74%
“…The clear correlations between our dv/v results with GRACE (Figure 2) and groundwater well measurements (Figure 3A) suggests that when the pore space of sedimentary rocks is filled with water during aquifer recharge, the increasing pore-pressure, and related decreasing effective confining pressure and rock rigidity, generates the reduction of near-surface seismic velocity (Dong & Lu, 2016;Qin et al, 2022). In contrast, the increasing confining pressure and rigidity during drought periods lead to increases in seis-mic velocity.…”
Section: Discussionmentioning
confidence: 54%
“…As a low-latitude inland state, surface water storage and snowfall are negligible in Oklahoma (Swenson et al, 2008), so groundwater storage and soil moisture are the major contributors to the TWS in Oklahoma. Negative correlations between groundwater levels and dv/v have been observed in California (Clements & Denolle, 2018;Mao et al, 2022;Qin et al, 2022) and Germany (Lecocq et al, 2017). Also, the spatiotemporal variations of seismic velocity, after projecting into 2-D maps by using coda wave sensitivity kernels (Mao et al, 2022), are coherent with the discharge and recharge of aquifers in California.…”
Section: Correlation With Groundwater Measurementsmentioning
confidence: 96%
“…Seismic velocity is a measure of rocks' elastic properties, which is sensitive to perturbations in fluid content, the stress field, and micro‐structures. Temporal changes in seismic velocity have been measured to study a variety of geological and environmental processes related to tectonic stress build up or release (Poupinet et al., 1984), magma storage changes at volcanos (Brenguier, Shapiro, et al., 2008; Koulakov et al., 2013; Mordret et al., 2010; Rivet et al., 2015), dynamic shaking or static stress changes caused by earthquakes (Brenguier et al., 2014; Froment et al., 2013; Peng & Ben‐Zion, 2006; Rubinstein & Beroza, 2004, 2005; Zaccarelli et al., 2011), seasonal changes in near‐surface saturation or groundwater level (Clements & Denolle, 2018; Clymer & McEvilly, 1981; Lecocq et al., 2017; Mao et al., 2022; Mordret et al., 2020; Qin et al., 2022; Sens‐Schönfelder & Wegler, 2006; Voisin et al., 2017), tidally induced strain (Mao et al., 2019; Takano et al., 2019; Wang et al., 2008; Yamamura et al., 2003), geothermal exploitation (Boitnott & Boyd, 1996; Sanchez‐Pastor et al., 2019; Taira et al., 2018; Zhang et al., 2022), CO 2 injection (Nakata et al., 2022), and freeze‐thaw cycles (James et al., 2019; Lindner et al., 2021).…”
Section: Introductionmentioning
confidence: 99%